Geliat Keberagamaan Moderat Komunitas Muslim Tionghoa (Kontribusi Pengkajian Islam Intensif dalam Keberagamaan Moderat Komunitas Muslim Tionghoa Kota Makassar) - Rosmini Rosmini; Syamsidar Syamsidar; Haniah Haniah (Al-Ulum, 2016)
Studying of the Qur'an continuously, integrated and comprehensively becomes a necessity if we want to practice the teachings of Islam â€œkaffahâ€. At least, this is the basis of dakwah implemented by the Chinese Muslim community in Makassar. One indicator of being â€œkaffahâ€ in embracing Islam is always showing moderate religious attitudes in all aspects of life, both individual and collective, at the level of faith, worship, muamalah, and morals. In understanding and practicing the teachings of Islam, the Chinese Muslim community in Makassar reflects religious moderation; therefore, their presence did not cause conflict in Makassar locally, but a blessing for the local community. Their Chinese identity is maintained by reconstructing the religious value of their traditions and culture. In this community, the belief of Islamic theology is not religiously indicated as elements of syncretism. As a result, their Chinese identity survives copes with their Islamic belief. Ultimately, moderate of Islamic teachings, as a religion of â€œrahmatan lil al alamiinâ€, is then reflected in their daily lives, including in their religious attitudes and behavior.